Lung Cancer Among Firefighters: Smoking-Adjusted Risk Estimates in a Pooled Analysis of Case-Control Studies. Issue 11 (November 2016) - Bigert, Carolina; Gustavsson, Per; Straif, Kurt; Taeger, Dirk; Pesch, Beate; Kendzia, Benjamin; Schüz, Joachim; Stücker, Isabelle; Guida, Florence; Brüske, Irene; Wichmann, Heinz-Erich; Pesatori, Angela C.; et al.
Abstract : Objectives: The aim of this study was to explore lung cancer risk among firefighters, with adjustment for smoking. Methods: We used pooled information from the SYNERGY project including 14 case-control studies conducted in Europe, Canada, New Zealand, and China, with lifetime work histories and smoking habits for 14, 748 cases of lung cancer and 17, 543 controls. We estimated odds ratios by unconditional logistic regression with adjustment for smoking and having ever been employed in a job known to present an excess risk of lung cancer. Results: There was no increased lung cancer risk overall or by specific cell type among firefighters ( n  = 190), neither before nor after smoking adjustment. We observed no significant exposure-response relationship in terms of work duration. Conclusions: We found no evidence of an excess lung cancer risk related to occupational exposure as a firefighter.